Pemeriksaan Antibodi Paska Vaksinasi COVID-19 pada Penduduk di Sekitar Universitas Jenderal Achmad Yani - Naully, Patricia; Nursidika, Perdina; Kania, Prina Puspa; Rachmawati, Firdha; Gunawan, Taufik (Universitas Nusantara PGRI Kediri, 2022)
In order to reduce the incidence of COVID-19, the Ministry of Health has thoroughly vaccinated including residents around Jenderal Achmad Yani University, but they don’t know the number of antibodies formed after the COVID-19 vaccination. This activity aims to provide information to residents around UNJANI regarding the number of specific antibodies that their bodies have successfully formed after the COVID-19 vaccination. A total of 50 local residents who have received the COVID-19 vaccination were invited to take part in this activity. Specific antibodies in the participants' blood were examined using the Enzyme Linked Immunosorbent Assay (ELISA) method. The results that have been validated by doctors are informed to the participants. Through laboratory examination, it was found that 66% of participants succeeded in forming specific antibodies above 7 U/ml and 34% of participants below 7 U/ml. The target of this activity has been achieved, residents around UNJANI can find out the number of specific antibodies they have successfully formed after the COVID-19 vaccination.